68Ga-FAPI PET/CT Detects Gastric Signet-Ring Cell Carcinoma in a Patient Previously Treated for Prostate Cancer. (August 2020) - Pang, Yizhen; Huang, Haichao; Fu, Li; Zhao, Liang; Chen, Haojun
Abstract : Abstract: A 75-year-old man with a history of prostate cancer (T1N0M0, Gleason score 4 + 3) was referred to radionuclide bone scan and 68 Ga-PSMA PET/CT to detect recurrence. Multiple abnormal foci were observed in the axial and appendicular skeleton, which were suggestive of metastatic superscan from prostate cancer. However, histopathological examinations (from bone biopsy) did not support the metastases from prostate cancer. 68 Ga-FAPI PET/CT was then performed to detect the occult tumor, which showed intense activity in the gastric wall. Subsequent gastroscopy examination revealed the diagnosis of GSRCC (gastric signet-ring cell carcinoma). The diagnosis of GSRCC with widespread bone metastases was finally made.